Studi Literatur: Faktor-Faktor yang Mempengaruhi Breastfeeding Self Efficacy - Putri Wulandari; Susilawati Susilawati; Sutrisno Sutrisno (Malang Journal of Midwifery (MAJORY), 2021)
The low rate of exclusive breastfeeding can be caused by various factors, including those from the mother, baby, and the environment. Mother's factors for not breastfeeding include the mother's self-confidence to breastfeed (Breastfeeding Self Efficacy). Four factors that influence breastfeeding self-efficacy are breastfeeding experience, observing other people's experiences, verbal persuasion and physical and emotional conditions. This study aims to describe the breastfeeding self-efficacy factors contained in the article under study. This literature study was obtained from searching scientific research articles from the 2010-2020 range using Google Schoolar. The results of the literature study obtained 48 articles, which after the identification, screening, and eligibility processes were carried out from 48 articles there were 7 articles that matched the inclusion criteria of the researcher. From the 7 articles studied, it was found that breastfeeding experience factors, observations of other people's experiences, verbal persuasion and physical and emotional conditions were related to Breastfeeding Self Efficacy. And of these 3 factors, verbal persuasion is the most dominant influencing, because persuasion in the form of support and enthusiasm will solve the problems faced can inspire breastfeeding mothers to be persistent and strong in increasing their self-efficacy Keywords : Breastfeeding, self efficacy, postpartum mothers